New approaches to reduce sample processing times for the determination of polycyclic aromatic compounds in environmental samples. (July 2021) - Xia, Zhe; Idowu, Ifeoluwa; Kerr, Evan; Klaassen, Nicole; Assi, Harsimran; Bray, Harley; Marvin, Chris; Thomas, Philippe J.; Stetefeld, Jorg; Tomy, Gregg T.
Abstract: This study validates two approaches to streamlining the processing of sediment and biota for a suite of polycyclic aromatic compounds (PACs) with a wide range of chemical properties, including polycyclic aromatic hydrocarbons (PAHs) and alkyl-PAHs (APAHs), and a new class of environmental contaminants, halogenated PAHs (HPAHs). One method is based on one-step in situ extraction/cleanup using accelerated solvent extraction (ASE) in which a mixture of copper, deactivated alumina and silica gel were added directly to the ASE cell along with sample; the second technique is based on dispersive solid phase extraction (dSPE) using alumina/silica for cleanup of biota samples to augment conventional ASE extraction combined with gel permeation chromatography. Validation protocols were performed in accordance with the ISO/IEC 17025 guidelines, whereby method performance characteristics, i.e., accuracy, precision, linearity, limits of detection and ruggedness, were evaluated. Accuracies generally ranged from 70 to 120% for the in situ ASE method and 70–100% for the dSPE technique. Limits of detection/quantitation for the 45 target analytes for in situ ASE and dSPE methods were determined to be < 2.5/8 pg μL −1, and < 20/60 pg μL −1, respectively. Intra- and inter-day repeatability for both methods were < 25% except for 1 APAH which had an inter-day precision of 35% using the dSPE method. Neither method was affected by any of the purposeful changes attempted which implies that both methods are robust. Results of our validation studies showed excellent data quality for both methods in addition to achieving a reduction in sample processing times. Graphical abstract: Image 1 Highlights: Validated two new approaches for analysis of 45 polycyclic aromatic compounds in environmental samples. Methods based on an in situ ASE for extraction and cleanup of sediment samples and a dSPE cleanup for biota. Accuracy ranged from 70 to 120% and repeatability <35% for both methods. LODs and LOQs were in the sub-ng μL −1 range. Both methods result in significant reduction in sample processing times.